KUALITAS DAN KOMPOSISI KIMIA SILASE JERAMI JAGUNG DENGAN PENAMBAHAN BERBAGAI JENIS ADITIF SILASE - Ria Anjalani; Paulini Paulini; Nyahu Rumbang (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
This study aims to determine the quality and chemical composition of corn straw silage with the addition of various silage additives. The study used a completely randomized design consisting of 4 treatments, namely P1 (corn straw + 10% rice bran), P2 (corn straw + EM4 10%), P3 (corn straw + 10% milled corn), and P4 (corn straw + tapioca flour 10%). Parameters observed are physical quality, fermentative quality, and chemical composition of corn straw silage. The results showed that the physical qualities of all treatments gave the same results. The pH and Fleigh Scores of all treatments show no significant difference (P>0.05). The content of DM, OM, and CP from all treatments show no significant difference (P>0.05),while the CF show a significant difference (P<0.05). From the results of this study, it is concluded that the addition of EM4 as a silage additive gave the best results on corn straw silage.